SPECTROSCOPIC INVESTIGATIONS OF GALACTIC CLUSTERS WITH ASSOCIATED CEPHEID VARIABLES. II. NGC 5662 AND V CEN - Usenko, I. A.; Kniazev, A. Yu.; Kovtyukh, V. V.; Mishenina, T. V.; Miroshnichenko, A. S.; Turner, D. G.; Protsyuk, Yu. I. (Одеські астрономічні публікації, 2018)
We present the results of a spectroscopic and photometric investigation of 15 objects from the open cluster NGC 5662, which contains the Cepheid V Cen. Besides the Cepheid, we studied one G-supergiant, two K-giants, four B-giants, and seven main sequence stars. Radial velocities (RV), v sin i, Teﬀ, log g, and [Fe/H] were determined using model ﬁtting. We have derived the color-excesses, reddenings, and intrinsic colors for these stars to determine their true Teﬀ and log g from comparison to the atmophere models, especially for hot stars, and to determine their absolute magnitudes. RV and GAIA DR2 2018 parallax/distance values for these stars allowed us to determine their membership in the cluster and to construct it 3D kinematic models. These parallaxes and reddenings led to the distances in a range of 700– 875 pc, while photometric MV gave the distances of 550–660 pc. Two objects from our list were found to be non-members of the cluster, and two other objects to be background stars. All members have [Fe/H] = −0.1±0.04 dex. The main sequence stars and B-giants have abundances of C, N, and Na close to the solar one, while the cool supergiants and giants show a deﬁcit of carbon, an overabundance of nitrogen, and a small overabundance or close to the solar sodium content. Two Li-rich K-giants, HD 127733 and HD 127753, were discovered in the cluster.